Twenty-Four-Hour Intraocular Pressure in Chronic Primary Angle-Closure Disease - Supakontanasan W. (2023)
PRCIS: Primary angle closure and primary angle closure glaucoma may exhibit normal intraocular pressure. Twenty-four-hour intraocular pressure fluctuation is highest in primary angle closure glaucoma. The degree of peripheral anterior synechiae was associated with a 24-hour intraocular pressure pattern in primary angle-closure disease without laser iridotomy. PURPOSE: The purpose of this study was to study 24-hour intraocular pressure (IOP) patterns in eyes with chronic primary angle-closure disease and evaluate associations between peripheral anterior synechiae (PAS) and 24-hour IOP pattern. PATIENTS AND METHODS: In this prospective cohort study, 59 eyes of 35 Asian patients with chronic primary angle-closure disease underwent complete ocular examinations at Ramathibodi Hospital, Mahidol University. Twenty-four-hour IOP records were obtained using Goldmann applanation tonometry at 2-hour intervals. Peak, mean, and trough 24-hour IOP values and 24-hour IOP fluctuation (difference between peak and trough values) were compared among groups. None of the participants received any treatment before complete data collection. RESULTS: Even univariable analysis demonstrated a significant difference in peak, mean, and trough IOP and 24-hour IOP fluctuation between the 3 groups; the magnitude of trough IOP was not higher than 21 mmHg in all groups. In multivariable analysis, PAC and PACG eyes showed significantly higher peak IOP ( P =0.020 and 0.006, respectively) and 24-hour IOP fluctuation ( P =0.048 and 0.001, respectively) compared with PACS eyes. In comparison between combined PACS and PAC eyes versus PACG eyes, PACG eyes revealed significantly higher 24-hour IOP fluctuation. The degree of PAS was associated with peak and mean IOP values and with 24-hour IOP fluctuation in PAC and PACG eyes. CONCLUSIONS: Twenty-four-hour IOP fluctuation was highest in PACG eyes. Although PAC and PACG eyes showed higher peak IOP and 24-hour IOP fluctuation values, compared with PACS eyes, trough IOP in PAC and PACG eyes were mostly below 21 mmHg. In addition, the degree of PAS was associated with a 24-hour IOP pattern in either PAC or PACG eyes.